ТӘБИЙИЙ ГЕОГРАФИЯНЫ ОҚЫТЫЎДА ДИДАКТИКАЛЫҚ МАТЕРИАЛЛАРДАН ПАЙДАЛАНЫЎ - Жиемуратова, Г. (FAN va JAMIYAT, 2016)
The article deals with some methods of teaching the elementary course of geography using the didactic materials to evaluate the pupils’ knowledge, skills and habits.